LA PERVIVENCIA DE LAS HEROÍNAS GRIEGAS EN EL TEATRO ARGENTINO CONTEMPORÁNEO: UNA REVISIÓN DEL MITO DE ELECTRA - Bravo de Laguna Romero, Francisco J. (Myrtia, 1999)
The aim of this study is to present the structures, topics and resources taken from the Greek dramatic tradition by modern playwrights. We have payed special attention on the importance of Greek heroines in such dramatic tradition, specially the case of Electra, the only one dealt writen by the three main Greek playwrights. This same topic of Electra have been raised again by another set of three Argentinian playwrights: Sergio de Cecco in El reñidero , Ricardo Monti in La oscuridad de la razón and Javier Roberto González in La declaración de Electra.